Characterization of Escherichia coli isolates potentially covered by ExPEC4V and ExPEC10V, that were collected from post-transrectal ultrasound-guided prostate needle biopsy invasive urinary tract and bloodstream infections. Issue 33 (14th July 2020) - Saade, Elie; Gravenstein, Stefan; Donskey, Curtis J.; Wilson, Brigid; Spiessens, Bart; Abbanat, Darren; Poolman, Jan; de Palacios, Patricia Ibarra; Hermans, Peter
Highlights: O-serotype prevalence in a tetravalent and decavalent ExPEC vaccine was studied. By both agglutination and PCR, prevalence was higher for the decavalent vaccine. Results also indicated protection against antibiotic-resistant ExPEC isolates. An ExPEC vaccine may have potential for prophylaxis of post-procedure infections. Abstract: There is an increasing incidence of infectious complications caused by extraintestinal pathogenic Escherichia coli (ExPEC) after transrectal ultrasound-guided prostate needle biopsy (TRUS-PNB), and a need for prophylaxis methods effective against associated antibiotic–resistant organisms. We aimed to identify the O-serotypes of ExPEC isolates collected in a sample of 60 patients with invasive ExPEC disease (IED) after TRUS-PNB, by serotype–specific agglutination and polymerase chain reaction (PCR) assays. The prevalence of O–serotypes included in a tetravalent ExPEC vaccine was 38.3% by agglutination and 46.7% by PCR, while the prevalence of O-serotypes included in a decavalent vaccine was 58.3% and 73.3%, respectively. Therefore, compared to the tetravalent vaccine, the decavalent vaccine would theoretically provide coverage for serotypes carried by a higher proportion of circulating ExPEC in patients undergoing TRUS-PNB, including a high proportion of antibiotic-resistant organisms.